Analysis of the Contribution of Utilization of Non-Wood Forest Products to the Income (Case Study at Some Village Communities Around the Forest of North Tapanuli Regency, North Sumatra, Indonesia) - Pandiangan, Donna Christy; Supriana, Tavi; Nuryawan, Arif (Journal of Sylva Indonesiana, 2023)
The contribution of forest in North Tapanuli Regency can increase the economic income of the local community through the use of Non-Wood Forest Products (NWFPs). Most village communities around the forests of North Tapanuli Regency have used NWFPs for generations to meet their needs. This study aims to analyze the value of the contribution of NWFPs to the income of village communities to determine the level of community dependence on these forest resources. Knowing the value of the contribution of NWFPs can be used as recommendations for policymakers to allocate increasingly scarce NWFPs and distribute the benefits of NWFPs fairly and optimally. This research was conducted in five Districts in North Tapanuli Regency considering that there are still many people who live depend on NWFPs. The research method was carried out by field observations and interviews using questionnaires, with a total sample of 98 respondents. Respondents were taken using the purposive sampling method. Respondent identification was done through the snowball technique. Data analysis of the contribution value was carried out by calculating the total income of the community, such as incomes sourced from NWFPs and other income. The results showed that the monthly income of villagers outside of NWFPs was in the range of IDR 1,000,000 “ 2,000,000. Then the contribution of NWFPs to the income of villagers around the forest was 74.9% of income outside of NWFPs